(untitled) (International Journal of Plant Biology, 2020)
This study aimed to analyze the structure and density of non-glandular trichomes and the area of cocoa leaves, and the differences of xylem vessel structures on various shade tree composition. The leaf area and length, and trichomes were observed. The xylem vessel structure was observed from the root system. The result showed the area of cocoa plots without shade tree has more varied leaves size, in which upper canopy was smaller than the bottom. The area with various shade had a relatively equal size between the upper and the lower of the canopy. The three stellate-shaped non-glandular trichomes were found on the leaf venations only with the density in two plots increased with time. The xylem width area to the whole root width area ratio (k) in various shade trees was lower (k= 0.641) than that of without shade trees (k= 0.718). The higher k values indicated xylem structure without the shade tree had more xylem cells, and the pores was smaller compared to the plot with various shade trees.